Feasibility study on retrieval of aerosol mask and optical depth. Final report of NWC SAF Visiting/Associated Scientist Activity - Musiał, Jan (2016)
Information about atmospheric aerosols is of great importance for all domains of optical remote sensing including satellite meteorology and climatology. For this reason improvements of the aerosol flag dataset derived by the EUMETSAT NWC SAF PPS version v2017/2018 software are to be implemented. In this scope, the EUMETSAT NWC SAF issued a feasibility study under the framework of Visiting Scientist (VS)/Associated Scientist (AS) activity. The study was organised into two 14 days VS activities at the beginning and at the end of the Project separated by 2 months of the AS activity. Time frame of the activity spanned from 30.05.2016 to 30.09.2016.
Keywords: aerosol mask; atmospheric aerosols; optical depth Retrieval